Комплекс озброєння дунайських болгар першої половини ІХ cт.: хазарський слід - Калініченко, Віталій (Чернівці, Видавничий дім "Букрек", 2016)
The era of the late of VIII – the first half of the IX-th century in Central, Southern and Eastern Europe richness of different events which made their changes in geopolitical living in the Carpathian-Danube region as a whole. It is then important changes took place in the military culture of various public entities that time, which resulted in their arms, tactics and strategy. The powerful military establishment and arms allowed them to carry out military expansion into regions with different military culture that led to the accumulation offs and military experience. Among the most powerful state formations beginning of the IX-th century was the First Bulgarian Empire. Important khan Krum was wars with the Byzantine Empire in the early IX-th century. They allowed khan better acquainted with the then military culture of Byzantium and, to some extent, to modernize its own army, which at that time had a nomadic character. Starting from 814 bulgarian khan became Omurtag who spent administrative reform and fighting in the south-west, and most importantly the north-eastern borders of the empire, resulting in contact with the military culture of the Khazar Khanate first quarter of the IX-th century. Archaeological studies indicate that since the beginning of the IX-th century. Bulgarians began quite actively explore the Dniester region, Prut more. Proof of this is the large number of villages on both banks of the river Dniester. Bulgarian khans had fairly large territories in the north and east of the country. In addition, they provide a fairly big deal for exploration and colonization of these territories, while holding an active policy of resettlement. If the events of the 20’s years IX-th century of more or less throw light on the military culture of the Danube Bulgarians during this period, the events of an earlier time in the north-eastern and eastern part of the Danube Bulgarian state, including 799-815 years today remains very controversial. Most likely, that at that time was one of the most important and key events in the Khazar Khanate, which indicates a close relationship in the military culture of the Khazars, Danube Bulgarians and other ethnic groups who were part of the Khazar Khanate and participating in various military campaigns. This is a civil war that broke out in the state the Khazars in the early IX-th century. Note that the relationship between the Khazar Khanate and the bulgarians were very close, as reflected in the latest weapons complex. The aim of this work is a comprehensive analysis of longrange weapons and melee Danube Bulgarians and overarching characteristic of relations between Bulgarians and Khazars in the military aspect of the first half of the IX-th century. Thus, during the late VIII – the first half of the IX-th century should be considered a transitional stage in the formation of a new military culture of the bulgarians, who was still nomadic. Huge impact in the aforementioned period had connections with the great-grand bulgarians Khazar Khanate, the territory of which the significant amount of armaments, characteristic of the First Bulgarian Empire, including weapons and long-range melee. This indicates that in the earlier period – in VII-VIII centuries. Bulgarian played an important role in the army of the Khazars, as evidenced by the discovery of weapons VIII-IX centuries. Overall, the first half of the IX-th century in general and the Civil War in the Khazar Khanate in particular, is an important period in the formation of the military culture of the Danube Bulgarians, which developed on the basis bulgars component with significant influence military culture of Byzantium and the Khazars. Migration that took place in the first half of the IX-th century played a great importance in the militarypolitical history of Central and Southeast Europe in the IX-th century in general.
Комплекс вооружения дунайских болгар первой половины ІХ в.: хазарский след
Armament systems of Danube Bulgaria first half of IX-th century: khazar influence
Keywords: Перша Болгарська держава; Хазарський каганат; військова справа; мілітарна культура; предмети озброєння